Slow-wave sleep is controlled by a subset of nucleus accumbens core neurons in mice - 裏出 良博; LAZARUS MICHAEL; Oishi Yo; Xu Qi; Wang Lu; Zhang Bin-Jia; Takahashi Koji; Takata Yohko; Luo Yan-Jia; Cherasse Yoan; Schiffmann Serge N.; de Kerchove d'Exaerde Alban; et al. (Nature communications, 2017)
Sleep control is ascribed to a two-process model, a widely accepted concept that posits homoeostatic drive and a circadian process as the major sleep-regulating factors. Cognitive and emotional factors also influence sleep–wake behaviour; however, the precise circuit mechanisms underlying their effects on sleep control are unknown. Previous studies suggest that adenosine has a role affecting behavioural arousal in the nucleus accumbens (NAc), a brain area critical for reinforcement and reward. Here, we show that chemogenetic or optogenetic activation of excitatory adenosine A2A receptor-expressing indirect pathway neurons in the core region of the NAc strongly induces slow-wave sleep. Chemogenetic inhibition of the NAc indirect pathway neurons prevents the sleep induction, but does not affect the homoeostatic sleep rebound. In addition, motivational stimuli inhibit the activity of ventral pallidum-projecting NAc indirect pathway neurons and suppress sleep. Our findings reveal a prominent contribution of this indirect pathway to sleep control associated with motivation.